Discussion at the Center for Global Development - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank, addressed the common challenge presented by slowing world growth. He remarked that governance issues are apparent around the world. On matters of debt, he emphasized dispute settlement, debt contract transparency, contract fairness, and facilitating better living standards. He noted that some countries’ debt payments are in arrears.